The Evaluation of Geroprotective Effects of Selected Flavonoids in Drosophila melanogaster and Caenorhabditis elegans - Lashmanova, Ekaterina; Zemskaya, Nadezhda; Proshkina, Ekaterina; Kudryavtseva, Anna; Volosnikova, Marina; Marusich, Elena; Leonov, Sergey; Zhavoronkov, Alex; Moskalev, Alexey (Frontiers in Pharmacology, 2017)
Flavonoids is an intensively studied group of natural compounds with antioxidant, antineoplastic, antihyperglycemic, cardioprotective, and neuroprotective properties. The present study intends to investigate the geroprotective action of three selected flavonoids (naringin, luteolin, chrysin) in two model organisms, Caenorhabditis elegans and Drosophila melanogaster. Luteolin and chrysin were shown to improve lifespan parameters when administered to both model organisms. The observed positive effects of these flavonoids in D. melanogaster were limited to females and were not associated with reduced fecundity or locomotor impairment. The life-extending effects of flavonoids were observed in N2 wild-type worms but absent in aak-2(gt33) mutants implying that these effects can be associated with AMP-activated protein kinase activity. Naringin improved lifespan parameters of C. elegans, but had no effect on D. melanogaster females; in some cases, naringin was found to decrease the lifespan of males. Compared to chrysin and luteolin, however, naringin more effectively activates Nrf2 target genes (particularly, GstD1) under oxidative stress. Then we compared molecular mechanisms of studied compounds and a well-known geroprotector rapamycin, using software tool GeroScope. There are no transcriptomic data on luteolin or chrysin provided by LINCS Project database. The bioinformatics comparison of transcriptomics data for A549 and MCF7 human cell lines treated with rapamycin or naringin revealed that these compounds share just a few common signaling pathways and quite distinct in their geroprotective action. Thus, based on C. elegans effects of naringin, luteolin, chrysin on lifespan we have revealed new potential geroprotectors.